The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1108/itp-02-2019-0092
|View full text |Cite
|
Sign up to set email alerts
|

Try-on experience with augmented reality comforts your decision

Abstract: Purpose The purpose of this paper is to understand how augmented reality (AR) try-on experiences facilitate consumers’ shopping decision. Focusing on the immersion and psychological ownership, the study investigated how the properties of AR experiences (environmental embedding (EE) and simulated physical control (SPC)) affect decision comfort. Design/methodology/approach This research theoretically and empirically analyzes how each property of AR experiences affects consequential psychological states and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 86 publications
4
40
0
1
Order By: Relevance
“…Thirdly , this study has highlighted the importance of the immersive experience or psychological state engaged in technological devices from a psychological perspective (e.g. Song et al., 2019 ), while other studies have focused on the characteristics of virtual devices in social or technological perspectives. In previous studies ( Flavián et al., 2019b ; Hilken et al., 2018 ), the immersive experience is only applied in education and game contexts in developed countries; there have been few studies investigating the usage of AR apps for marketing purposes.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Thirdly , this study has highlighted the importance of the immersive experience or psychological state engaged in technological devices from a psychological perspective (e.g. Song et al., 2019 ), while other studies have focused on the characteristics of virtual devices in social or technological perspectives. In previous studies ( Flavián et al., 2019b ; Hilken et al., 2018 ), the immersive experience is only applied in education and game contexts in developed countries; there have been few studies investigating the usage of AR apps for marketing purposes.…”
Section: Discussionmentioning
confidence: 95%
“…This study has some significant contributions. Firstly, previous studies have utilized only one product or an AR app for their research in retail settings (e.g., Song et al., 2019 ; Jessen et al., 2020 ); this study reviews the applications of AR technology in marketing contexts from a number of countries and intends to propose a comprehensive conceptual model for AR apps. Secondly , previous studies have discussed customer experiences through AR features and the motivations of customers using AR apps ( Yim et al., 2017 ; Poushneh, 2018 ; Hsu et al., 2021 ), but few studies have specifically examined the impact of customer traits as personal innovativeness and mental imagery on the immersive experience.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, more cognitive resources are available for building cognitive associations. Song et al [14] found that EE and SPC positively affect customers' decision comfort by evoking customers' perceived immersion. Decision comfort refers to the degree of ease, contentment, and wellbeing one feels when making a specific decision and is a soft-positive emotion [15].…”
Section: Research Hypothesesmentioning
confidence: 99%